Classical intertextual co-inheritance. Hermeneutical reading of some elements of the Greek tragedy Hippolytus in Desire under the elms by Eugene O'Neill - Monge Ortiz, Jorge A. (2023)
This paper proposes the intertextual relationship that reveals some elements of the Greek myth in the dramaturgy of the 20th century. Eugene ONeill was a representative American writer in this sense. It is a discursive reading of the search in the form and content of textual polysemy, in dramaturgy as a dialectical, anachronistic and synchronic phenomenon at the same time and in the co-inheritance that the presence of the Greek myth still has today.It starts from the cyclical process of transcendental thematic reading that has arisen in drama over time.The hermeneutic reading arises in the Greek myth of Hippolytus in the drama of Euripides which, in turn, refers to both the myth of Phaedra and Medea, who are heroines who kill their children; and Hippolytus's rejection of the goddess Aphrodite in his representation of the force of Eros in relation to one of O'Neill's most representative works: Desire under the elms.